Systematic Review of Fatigue in Individuals With Cerebral Palsy - Puce, Luca; Pallecchi, Ilaria; Chamari, Karim; Marinelli, Lucio; Innocenti, Tiziano; Pedrini, Riccardo; Mori, Laura; Trompetto, Carlo (Frontiers in Human Neuroscience, 2021)
In this systematic review, we collected and analyzed literature works comparing self-reported fatigue and objectively-measured fatigue in individuals with cerebral palsy (CP) and in age-matched typically developing/typically developed (TD) controls. The search was conducted on four electronic databases/platforms (PubMed, Web of Science, Cochrane Library (CENTRAL), Scopus) using the key words “cerebral palsy” combined with “fatig*”, where the asterisk was used as a wildcard. As a critical appraisal tool, the Joanna Briggs Institute Critical Appraisal Checklist for Quasi-Experimental Studies (2017) was used. A total of 22 studies passed the critical appraisal rating and were included in both narrative and quantitative analyses. The overall evidence quality of the findings was considered very good. Data of objectively-measured fatigue in performing maximal fatiguing tasks indicated lower fatigue levels in participants with CP, possibly due to their pathological inability to recruit highly fatigable muscle fibers. Highly trained individuals with CP and TD controls performing maximal fatiguing tasks seem to be an exception to this, as they exhibited similar levels of fatigue. In submaximal fatiguing tasks, including daily physical activities, either objectively-measured or self-reported fatigue was higher in participants with CP than in TD controls, indicating a lower ability for development of neurophysiological compensation for fatigue among participants with CP. Further studies on fatigue are needed to gain an insight into the multifold mechanisms of fatigue in individuals with CP. Understanding fatigue mechanisms could help in setting up strategies for effective intervention programs, with benefits in healthcare and improved quality of life of individuals with CP. Systematic review registration number PROSPERO 2019: CRD42019143524